2011
DOI: 10.1242/dev.057778
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Kcnq1ot1 non-coding RNA does not affect imprinting maintenance in stem cells

Abstract: SUMMARYTo understand the complex regulation of genomic imprinting it is important to determine how early embryos establish imprinted gene expression across large chromosomal domains. Long non-coding RNAs (ncRNAs) have been associated with the regulation of imprinting domains, yet their function remains undefined. Here, we investigated the mouse Kcnq1ot1 ncRNA and its role in imprinted gene regulation during preimplantation development by utilizing mouse embryonic and extra-embryonic stem cell models. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 53 publications
7
73
0
Order By: Relevance
“…Using this approach, Okae et al established reciprocal F1 TS cells between B6 and JF1 mice and demonstrated imprinted expression of the Megs Tspan32 and Tfpi2, after confirming appropriate maintenance of imprinted expression at 10 known imprinted genes. Together with similar recent studies carried out on reciprocal [B6xCAST]F1 TS cells (Golding et al, 2011), the imprinted expression of 20 genes have now been confirmed in the trophoblast lineage using TS cells (Table 1). Those results are important since they establish that epigenetic imprinting marks are stably maintained in TS cells in culture, which therefore represent an important model system to study imprinted gene regulation and function in this lineage.…”
Section: Maternally Expressed Imprinted Genes In the Placentasupporting
confidence: 76%
See 1 more Smart Citation
“…Using this approach, Okae et al established reciprocal F1 TS cells between B6 and JF1 mice and demonstrated imprinted expression of the Megs Tspan32 and Tfpi2, after confirming appropriate maintenance of imprinted expression at 10 known imprinted genes. Together with similar recent studies carried out on reciprocal [B6xCAST]F1 TS cells (Golding et al, 2011), the imprinted expression of 20 genes have now been confirmed in the trophoblast lineage using TS cells (Table 1). Those results are important since they establish that epigenetic imprinting marks are stably maintained in TS cells in culture, which therefore represent an important model system to study imprinted gene regulation and function in this lineage.…”
Section: Maternally Expressed Imprinted Genes In the Placentasupporting
confidence: 76%
“…The genes are sorted by chromosomal position. The data from three recent studies, including two genome-wide RNA-seq analyses of placental imprinted genes, are summarized (Golding et al, 2011;Okae et al, 2011;Wang et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…As the relaxation of imprinting of genes within the Kcnq1 locus remains similar between the deletions encompassing Kcnq1 ICR (3.0 kb), Kcnq1ot1 promoter (246 bp) or the truncation of the Kcnq1ot1 transcript that retains 3.0 kb ICR (Mancini-Dinardo et al, 2006), the observed loss of transcriptional silencing of UIGs is mainly due to conditional depletion of Kcnq1ot1 RNA rather than other functional elements within the Kcnq1 ICR. In a recent investigation, by posttranscriptionally depleting Kcnq1ot1 RNA using a short hairpin RNA (shRNA) in cultured ES cells it was demonstrated that Kcnq1ot1 ncRNA is not required to maintain imprinted silencing of the UIGs (Golding et al, 2011). As these experiments were performed in cultured cells, and for a snapshot of time, it is not clear how well they represent the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…The Kcnq1ot1 imprinted domain spans a 1 Mb region in mice and is characterized by a maternally methylated ICR and two paternally methylated secondary somatic DMRs (at and upstream of the Cdkn1c gene) (Yatsuki et al 2002;Bhogal et al 2004;Lewis et al 2004;Umlauf et al 2004;Golding et al 2011;Mohammad et al 2012) (Fig. 2).…”
Section: Tads At Imprinted Domainsmentioning
confidence: 99%